Problematic schooling: simulation or phobia? (Journal of Parents and Teachers, 2024)
The article discusses the importance of the family and social environment in children's emotional development, emphasizing how anxiety can affect their educational experience. It references Winnicott's theory, which highlights the significance of the relationship between the child and their surroundings. Additionally, it suggests that adults should be mindful of their actions and emotions to prevent children from feeling guilty or anxious. In conclusion, it underscores the need for appropriate emotional support for children's well-being.
Keywords: environment; emotional; anxiety; support